2019
DOI: 10.2478/helm-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coffee silver skin and brewers’ spent grain in the control of root-knot nematodes

Abstract: SummaryPlant parasitic nematodes (PPN) are important pests of numerous agricultural crops especially vegetables, able to cause remarkable yield losses correlated to soil nematode population densities at sowing or transplant. The concern on environmental risks, stemming from the use of chemical pesticides acting as nematicides, compels to their replacement with more sustainable pest control strategies. To verify the effect of aqueous extracts of the agro-industry waste coffee silverskin (CS) and brewers’ spent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Thiligene et al investigated the effect of aqueous coffee silver skin extract on the root knot nematode Meloidogyne incognita [ 87 ]. The extract was shown to reduce the nematode population, but was less effective than a nematicide.…”
Section: Compositional and Toxicological Data On Coffee Silver Skinmentioning
confidence: 99%
“…Thiligene et al investigated the effect of aqueous coffee silver skin extract on the root knot nematode Meloidogyne incognita [ 87 ]. The extract was shown to reduce the nematode population, but was less effective than a nematicide.…”
Section: Compositional and Toxicological Data On Coffee Silver Skinmentioning
confidence: 99%
“…We found only one paper in biopesticides applications with CS. Thligene et al [102] demonstrated that silverskin significantly reduced the nematode population in tomato harvests. As mentioned in the section on bioactive compounds, the presence of several polyphenols, terpenes, and caffeine in CS (that are not usually present in the feed sources of these nematodes) could be the reason for why the extracts act as pesticides and, what is more, how they could also provide protection to the fruit due to their antimicrobial properties [47].…”
Section: Biopesticidesmentioning
confidence: 99%
“…The use of synthetic nematicides is considered the most effective practical means of combating the menace of plant-parasitic nematodes [15]. On the other hand, indiscriminate use of synthetic pesticides for controlling nematodes will likely lead to phytotoxicity, environmental pollution and nematode resistance [16][17][18][19]. Crop productivity can be enhanced with the use of bio-nematicides in place of the environmentally unsafe synthetic nematicides used in the control of plant parasitic nematodes [20].…”
Section: Introductionmentioning
confidence: 99%